(untitled) (Bangladesh Journal of Medical Education, 2025)
Background: In recent years, transition towards competency-based education, has been one of the most major shifts in medical education. From traditional lecture-based teaching-learning to problem-based teaching-learning (PBL), flipped classroom learning (FCL) and team-based teaching-learning (TBL) are the methods increasingly being employed in medical education. For promoting active learning by improving teaching efficiency is the most valuable and effective approach, which requires students to actively participate in the class, engage with learning materials and collaborate with the peers This study aimed to evaluating the effectiveness and acceptability of Traditional Lecture-Based Learning (TLBL) and Flipped Classroom Learning (FCL) in dermatology among undergraduate medical students of Bangladesh. Methods: This quasi experimental study was performed among 118 undergraduate medical final year students from three non-government medical colleges in Cumilla district of Bangladesh, who were selected using convenience sampling method. The study was conducted from July 2023 to June 2024. To assess effectiveness three topics Acne, Psoriasis and Alopecia were chosen and two teaching methods Traditional Lecture-Based Learning (TLBL) and Flipped Classroom Learning (FCL) were adopted. Pre-test and Post-test of each session were conducted and self-administered structured questionnaire were used to get level of performance and satisfaction respectively. Results: Study revealed that the overall satisfactions about the attainment of ‘learning objectives’, ‘learning ability and interest’, ‘team/group work ability’, ‘clinical ability’ and on the ‘teaching method’ by TLBL were 43.2%, 37.4%, 25.6%, 37.4% and 44.2 % respectively; These satisfactions were increased as 75%, 77.4%, 74.4%, 77.8% and 75.8% respectively by FCL. The gross satisfaction in percentage with TLBL was 37.6% and was increased to 76% with FCL. All these differences were statistically significant between the two groups as a whole (Independent t test, P=0.000). The mean post-class test scores compared to the mean pre-class test scores showed that students’ learning increased 85.83% by FCL (P=0.000) and decreased 4.22% by TLBL (P=0.6980).Conclusion: The null hypothesis of the of the present quasi experimental design was, ‘Traditional lecture-based leaning (TLBL) and Flipped classroom learning (FCL) are equally effective in teaching dermatology to undergraduate medical students of Bangladesh’. Based on the findings of the present study we can reject the null hypothesis and accept the alternate hypothesis ‘Flipped classroom learning and Traditional lecture-based leaning are not equally effective; Flipped classroom learning is better than Traditional lecture-based learning in teaching dermatology to undergraduate medical students of Bangladesh.’. FCL can be complementary with TLBL if these are judiciously used and included with wider research in the teaching methods of medical education of Bangladesh. BJME, Volume-16, Issue-02, July 2025: 10-23